IMR 665: Management of Audio Visual Records & Archives. Individual assignment: Article summary / Nur Izzamul Izyan Muhammad Sharif - Muhammad Sharif, Nur Izzamul Izyan (2015)
Article on: Article 1 - “Audio-visual preservation: A perpetual dilemma among selected Philippine academic libraries” Article 2 – “The Case for Digital Preservation of the Press and Audio-Visual Documents in Mauritius”